Information needs and preferences among rural cancer survivors in Queensland, Australia: a qualitative examination - Fiona Crawford‐Williams; Belinda C. Goodwin; Suzanne K. Chambers; Joanne F. Aitken; Martelle Ford; Jeff Dunn (Elsevier, 2022)
Abstract Objective: This study aimed to understand how cancer survivors in rural Queensland seek and receive information, as well as their preferences regarding the content and delivery of health‐related information. Methods: This study explored cancer survivors' experiences in seeking and comprehending health information using a qualitative descriptive approach. Semi‐structured interviews were conducted with 24 participants. Data were analysed using reflexive thematic analysis. Results: Two major themes and six sub‐themes were identified including 1) information content and gaps - a) information about diagnosis and treatment, b) survivorship information gaps and c) practical support needs and 2) delivery and acceptance of information - a) sources of information, b) personalised information needs and c) information seeking or avoidance. Findings suggested that health information provision was inconsistent; survivors' attitudes towards seeking information varied greatly; and survivors' had difficulty processing information due to emotional distress. Conclusion: The role of the health professional is critical in providing information and support to rural cancer survivors. Information provided should be tailored to meet the needs and preferences of individuals taking into consideration demographic factors and attitudes. Implications for public health: The current findings imply that quality information provision after cancer treatment would facilitate improvements in satisfaction among rural cancer survivors.